Pediatric Veno-Veno Extracorporeal Membrane Oxygenation Rescue From Carbon Monoxide Poisoning. Issue 10 (October 2020) - Baran, David A.; Stelling, Kelly; McQueen, Derrick; Pearson, Mark; Shah, Vaishali
Abstract : Background: Carbon monoxide poisoning affects approximately 5000 children per year and can be challenging to diagnose and treat ( Pediatr Emerg Med Pract . 2016;13:1–24). It is in the differential diagnosis of a patient presented with altered consciousness. Patients may look quite "pink" and well perfused, but are often in serious distress. We present the first case in the literature of carbon monoxide poisoning treated with the use of veno-veno extracorporeal membrane oxygenation (ECMO). Case: We report the case of a 10-year-old patient who had carbon monoxide poisoning (carboxyhemoglobin of 18%). She was treated with hydroxocobalamin at 70 mg/kg and was being prepared to transfer to a facility that offered hyperbaric therapy when she suffered a cardiac arrest requiring cardiopulmonary resuscitation. After 11 minutes of resuscitation, she had return of spontaneous circulation and an echocardiogram showed reasonable cardiac function. She was judged too unstable for ambulance transport and the ECMO team was called. Veno-veno ECMO was placed via a single right internal jugular dual-lumen catheter with fluoroscopy in the cardiac catheterization laboratory. There was a rapid improvement in carboxyhemoglobin level, and the ECMO therapy was weaned the next day. The patient eventually made a full recovery. Conclusions: This is the first time that veno-veno ECMO has been reported for the emergent treatment of carbon monoxide intoxication. If emergency physicians are treating such a patient and cannot administer hyperbaric oxygen therapy, ECMO represents a valuable alternative that is not commonly thought of in this situation before.